U.S. International Equity Investment - AMMER, JOHN; HOLLAND, SARA B.; SMITH, DAVID C.; WARNOCK, FRANCIS E. (Journal of Accounting Research, 2012)
ABSTRACT Using a comprehensive data set of all U.S. investment in foreign equities, we find that the single most important determinant of the amount of U.S. investment a foreign firm receives is whether the firm cross‐lists on a U.S. exchange. Correcting for selection biases, cross‐listing leads to a doubling (or more) in U.S. investment, an impact greater than all other factors combined. Much of this increased U.S. investment is purchased in the foreign market, implying that the cross‐listing effect reflects something more fundamental about a firm than easier acquisition of its securities. We also demonstrate that cross‐listing is an important determinant of U.S. international investment at the country level and describe easy‐to‐implement methods for including a cross‐listing variable as an endogenous control.